LEUKEMIA IN ERYTHROID BLAST CRISIS AND AUTOIMMUNE HEMOLYTIC ANEMIA: A CASE REPORT - Sierra, Yamilé Quintero; Padrón , Carlos Hernández; Fernández , Yusleidy Concepción; González , Adrián Romero (International Journal of Multidisciplinary Research and Studies, 2022)
Introduction: Chronic myeloid leukemia is a chronic myeloproliferative neoplasm characterized by the uncontrolled proliferation of myeloid precursors and autoimmune hemolytic anemia is an unregulated immune reaction towards the antigens themselves that are on the surface of the membrane of red blood cells. The combination of these diseases is extremely rare and even greater when chronic myeloid leukemia is in an erythroid blast crisis. Objective: To describe a case with the coexistence of chronic myeloid leukemia in erythroid blast crisis and autoimmune hemolytic anemia. Clinical case: Patient with a history of chronic myeloid leukemia who presents an erythroid blast crisis and develops autoimmune hemolytic anemia due to warm IgG antibodies. The treatment for both diseases will be administered. After a clinical improvement of the autoimmune hemolytic anemia, he maintained the erythroid blast crisis and was administered an intensive chemotherapy regimen where complications occurred and he died. Conclusions: The treatment with steroids in autoimmune hemolytic anemia in patients with chronic myeloid leukemia is effective when they are in the chronic phase of the disease, but is little responsive when they are in blast crisis, as was the case we present, and the fatal outcome in the patient was multifactorial.